Rethinking Cultural Competence: The Chair's Leadership Role - Edna Chun (Academic Chairpersons Conference Proceedings, 2017)
The seminar would focus on the ways that department chairs can strengthen the attainment of cultural competence through curricular offerings, course-based service learning, and faculty development.
Keywords: attainment of cultural competence; curricular offerings